Capacity for Innovation: Among Leading Industrial Countries, Germany Only Manages a Middle Rank - Heike Belitz; Axel Werwatz (Weekly Report, 2006)
The capacity of people and companies to bring about innovations, that is, to create new knowledge and implement this in new marketable products and services, is of prominent importance for growth and prosperity in highly developed industrial countries. On commission of Deutsche Telekom Stiftung and Bundesverband der Deutschen Industrie (BDI, Federation of German Industries), DIW Berlin has prepared an overall indicator of innovative capacity for the first time this year, in which Germany and 12 other leading industrial countries are studied. Germany takes sixth place following frontrunner USA, three Scandinavian countries and Japan, but does not have any clear advantages over the other large European countries, Great Britain and France.
Keywords: 330